Do the core symptoms play key roles in the development of problematic smartphone use symptoms - Huang, Shunsen; Lai, Xiaoxiong; Li, Yajun; Dai, Xinran; Wang, Wenrong; Li, Jing; Wang, Huanlei; Li, Dufang; Wang, Yun (Frontiers in Psychiatry, 2022)
Aims: Previous research determined the core symptoms (loss of control and being caught in the loop) of problematic smartphone use (PSU), which are of great importance to understand the structure and potential intervention targets of PSU. However, the cross-sectional design fails to reveal causality between symptoms and usually conflates the between- and within-subjects effects of PSU symptoms. This study aims to determine whether the core symptoms of PSU indeed dominate the future development of PSU symptoms from longitudinal between- and within-subjects levels. Methods: In this study, 2191 adolescents were surveyed for three years for PSU symptoms. A cross-lagged panel model (CLPM) was used to explore longitudinal between-subjects causal relationships between symptoms, and a graphic vector autoregressive model (GVAR) was used to separate the between- and within-subjects effects and detect the longitudinal effect at the within-subject level. Results: The results of CLPM indicated that the core symptoms (both loss of control and being caught in the loop) of PSU indeed dominate the future development of PSU symptoms at a longitudinal between-subjects level. From T1 to T2, the cross-lagged model showed that both the loss of control (out-prediction=.042) and being caught in the loop (out-prediction=.053) at T1 have the highest out-prediction over other symptoms at T2. From T2 to T3, the loss of control (out-prediction=.027) and being caught in the loop (out-prediction=.037) at T2 also have the highest out-prediction over other symptoms of PSU at T3. While, after separating the between- and within-subjects effects, only being caught in the loop at T1 played a key role in promoting the development of other PSU symptoms at T3 at the within-subjects level. The contemporaneous network showed intensive connection while the cross-sectional between-subjects network is very sparse. Conclusions: These findings not only confirm and extend the key roles of core symptoms in the dynamic aspect of PSU symptoms and PSU itself, but also suggest that interventions should consider the core symptoms of PSU, individual- and group-level effects, and that individualized intervention programs are needed in the future.